Integrasi Kurikulum Pendidikan Agama Islam Dalam Pembelajaran Farmasi - Dwi Prasetyo Adi; Suko Susilo; Titin Widya Risni (LPPM Institut Pendidikan Nusantara Global, 2026)
The integration of the Islamic Religious Education (PAI) curriculum into pharmacy learning is a relevant academic issue because pharmacy education is closely related to patient safety, professional accountability, and ethical decision-making, while PAI is often positioned as a separate general course. This study examines the integration of the PAI curriculum in pharmacy learning, with specific attention to first-semester pharmacy learning at Universitas Kadiri. The research employed a qualitative descriptive approach through literature review and document-based analysis of relevant curriculum, learning, and previous study materials. Data were analyzed by identifying recurring themes, classifying concepts of Islamic values and pharmacy ethics, and interpreting their relevance to contextual learning. The findings show that PAI integration can reduce the dichotomy between religious and scientific knowledge by internalizing values of honesty, trustworthiness, responsibility, discipline, empathy, and professionalism in pharmacy education. The integration may be implemented through Islamic-based professional ethics materials, case-based learning, lecturer role modelling, and laboratory habituation. Nevertheless, its implementation is constrained by limited interdisciplinary competence, insufficient contextual teaching materials, limited course duration, and the gap between students’ understanding of Islamic values and their application in academic behavior. This study recommends strengthening integrative learning models and academic culture to support the continuous internalization of Islamic values in pharmacy education.